The Advantages and Disadvantages of Transit-Oriented Development Area - Emily Yong Li Yu; Ainur Zaireen Zainudin (Research in Management of Technology and Business, 2024)
In recent years, Transit Oriented Development (TOD) has become a prominent land development concept in urban areas in Malaysia. TOD is a compact, mixed-use development near a transit station with high-quality walking environments. This concept offers a lot of benefits to urban dwellers but with certain trade-offs. Therefore, this paper aims to discuss the advantages and disadvantages of TOD based on systematic reviews of secondary data that include journal articles, newspaper articles and reports, as well as books. The advantages and disadvantages are discussed within the context of related variables encompassing the physical, environment, social and economic variables. Overall, it can be seen that TOD does have positive and negative implications, especially for property value